Empiric dimension of Aesthetic in School Education - Gordo Contreras, Aurora; Igua Muñoz, Joan Sebastián (Universidad Pedagógica y Tecnológica de Colombia, 2017)
According to global findings about school effectiveness, it is necessary to comprehend logical operators, dynamics and sociocultural influence on school populations. This evidences the sociological contribution of aesthetic field in order to asset the effects in the social interaction of school communities with their cultural environment. The present study aims to stablish what types of relations, impacts and marks of an educational context coexist in the behavior, tendency and social-aesthetic behavior at two different school sectors, as well as what conditional factors has influence on these phenomena. And if they appear symmetrical or asymmetrical. 312 matrixes were analyzed through the Mandoky’s Octadic Model. 30 students were involved in 156 objects and 156 activities during 16 activities. First grade students of Gimnasio Galileo Galilei and Escuela Rural del sur. The results show significant correlations of interinstitutional reproductive esthesis, thematic patterns of action and distinct influences of conditional factors by school sectors